Current global status & impact of human papillomavirus vaccination: Implications for India - Rengaswamy Sankaranarayanan (Indian Journal of Medical Research, 2016)
This review addresses the effectiveness and safety of human papillomavirus (HPV) vaccines, the current status of its introduction in the National Immunization Programmes (NIPs) and its relevance to India, which contributes a fifth of the global burden of cervical cancer. The vast literature on efficacy, acceptability and safety of HPV vaccination and its impact after population level introduction was reviewed and discussed. The efficacy of HPV vaccines in preventing high-grade precancerous lesions caused by vaccine-targeted HPV infections was 90 per cent or higher in HPV naοve women in randomized clinical trials. Two doses at 6 or 12 months apart are recommended for 9-14 yr old girls and three doses over six months to one year period for those aged above 15 yr. More than 80 countries or territories have introduced HPV vaccination in their NIPs, of which 33 are low- and middle-income countries (LMICs); in addition, 25 LMICs have introduced pilot programmes before a phased national expansion. Significant reductions in the frequency of HPV 16 and 18 infections, genital warts and cervical premalignant lesions in vaccinated cohorts and herd immunity in general populations have been reported from countries that introduced vaccination in NIPs as early as 2007. More than 280 million doses of HPV vaccines have been administered worldwide with the excellent safety profile with no serious adverse events linked to it. The high burden of cervical cancer and the high efficacy and safety of HPV vaccination justify its introduction in the Indian NIP at the earliest possibility to substantially reduce the cervical cancer burden in future.